Istotne czynniki warunkujące poziom opanowania języka obcego - Nieścioruk, Julia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It is undeniable that a wide variety of factors, both learner-internal and learner-external, influence the rate and level at which a language is mastered. From the two groups of factors, selected ones are presented, from learner-internal: well-being and foreign language enjoyment, and from learner-external: peer environment and relationship. The definitions of these factors are followed by a discussion of their correlation with other positive psychology factors and existing research results.
Keywords: radość z nauki języka obcego (FLE); determinacja; dobrostan psychiczny; psychologia pozytywna w nauce języków obcych; teoria złożonych systemów dynamicznych (CDST) w nauce języków obcych; środowisko rówieśnicze; relacje z rówieśnikami; foreign language enjoyment (FLE); well-being; positive psychology in foreign language learning; Complex Dynamic Systems Theory (CDST) in foreign language learning; peer environment; relationship